KNOWLEDGE, ATTITUDE, AND PRACTICE ON HOSPITAL ACQUIRED INFECTION (HAIs) PREVENTION AMONG THE UNIMAS UNDERGRADUATE NURSING STUDENTS - CHUNG, WUI CHIAT (Universiti Malaysia Sarawak, (UNIMAS), 2024)
Introduction: Hospital acquired infection (HAIs) also known as nosocomial infections, are infections that patients acquire during their stay in a hospital or other healthcare facility, which were not present or incubating at the time of admission. These infections can occur in various clinical settings, including acute care hospitals, long-term care facilities, and outpatient clinics. HAIs pose a significant challenge to healthcare systems worldwide, impacting patient outcomes, increasing healthcare costs, and contributing to higher morbidity and mortality rates. Healthcare worker is at the risk of infection spreading including nursing students during their clinical attachment in the healthcare setting. Objectives: This study aimed to assess the level of knowledge, to identify the attitude, to assess the level of practice and to examine the relationship between knowledge, attitude and practice on hospital acquired infection (HAIs) prevention among the UNIMAS undergraduate nursing students. Methodology: Descriptive cross-sectional quantitative study was conducted among the undergraduate nursing students in Universiti of Malaysia Sarawak. A total of 136 participants were selected using simple random sampling method. The data collection tool consisted of 39 item self-administered questions which divide into 4 parts, sociodemographic, level of knowledge, attitude, and level of practice on hospital acquired infection (HAIs) prevention. Data collected from this study was analyzed using IBM SPSS version 27. Results: Most of the nursing students demonstrated a good level of knowledge (91.63%), attitude (85.02%) and practice (77.14%). Further analyses revealed significant correlation between knowledge and attitude (r=.207, p=0.16), knowledge and practice (r=.329, p<.001) and attitude and practice (r=.360, p<.001). iv Conclusion: UNIMAS undergraduate nursing students showed a good level of knowledge, attitude and practice on hospital acquired infection (HAIs). However, there is the need to regular assessment and feedback sessions to continuously improve the curriculum and training methods.